2012
DOI: 10.1002/ar.22510
|View full text |Cite
|
Sign up to set email alerts
|

Canine Oral Mucosal Fibroblasts Differentiate into Osteoblastic Cells in Response to BMP‐2

Abstract: Several lines of evidence show that transplantation of osteoblastic cells or genetically engineered nonosteogenic cells expressing osteoblastrelated genes into bone defects effectively promotes bone regeneration. To extend this possibility, we investigated whether oral mucosal fibroblasts are capable of differentiating into osteoblastic cells by conducting in vitro and in vivo experiments. We investigated the effects of bone morphogenetic protein-2 (BMP-2) on osteoblast differentiation of cultured fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 170 publications
2
8
0
Order By: Relevance
“…We observed a hard tissue regeneration capacity even in the subcutaneous region. Umehara et al reported that canine oral mucosaderived fibroblasts could effectively differentiate into osteoblasts in response to BMP-2 [51]; thus, their findings support the results of our study. However, we did not observe tumor formation [4].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a hard tissue regeneration capacity even in the subcutaneous region. Umehara et al reported that canine oral mucosaderived fibroblasts could effectively differentiate into osteoblasts in response to BMP-2 [51]; thus, their findings support the results of our study. However, we did not observe tumor formation [4].…”
Section: Discussionsupporting
confidence: 92%
“…Various authors report that co-culture with osteoblasts [87] or treatment with BMP-2 or -7 [112,113] can induce fibroblasts to express typical osteoblast genes such as ALP and OCN, improving tendon-to-bone integration [113]. In addition, fibroblasts have also been reported to transdifferentiate into chondrocytes when transfected with Sox9 [114] or stimulated with cartilage-derived morphogenetic protein 1 (CDMP1) [115].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Cbfα1 is a key transcription factor and regulator of osteogenic differentiation, which may also regulate the expression of other osteogenic differentiation marker genes and osteogenic phenotype related genes such as alkaline phosphatase (ALP), OC, type I collagen, thereby enhancing the expression of osteogenic phenotypes to promote osteogenic differentiation and bone formation (23)(24)(25). Thus, the increased expression of Cbfα1 protein in fibroblasts is usually considered to be a sign of the osteogenic differentiation of fibroblasts, whereas the decreased expression of Cbfα1 may indicate the suppression of osteogenic differentiation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Cbfα1 protein expression has been demonstrated to be markedly increased in fibroblasts compared to the fibroblasts without BMP-2 induction, which are differentiated into osteogenic cells in response to BMP-2 (20). Notably, it has been reported that the expression of Cbfα1 is regulated by the BMP signal pathway (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation